Drought-Salinity-Waterlogging: Which is more deleterious for sustainable intensification in the coastal polder zone of Bangladesh - Mondal, Manoranjan (International Rice Research Institute, 2024)
The presentation tackles the relative impacts of drought, salinity, and waterlogging on sustainable intensification in Bangladesh's coastal polder zone.